Analysis of Students’ Creative Thinking Ability by Utilizing the Environment in Economics Subjects at SMA Negeri 1 Air Sugihan, Ogan Komering Ilir - Kamsiti, Kamsiti (PPSDP International Journal of Education, 2024)
In this study at SMA Negeri 1 Air Suguhan Organ Komering Ilir, we examined students’ imaginative capacity to utilize the environment for economic issues. The question of this research was how the environmental changes of SMA Negeri 1 Air Suguhan Ogan Komering Ilir could be applied to the creative thinking abilities of students for business problems. The factors in this think about were imagination considering and environment. An expressive strategy was utilized in this consideration. The test comprised of his 53 understudies from SMA Negeri 1 Air Suguhan Ogan Komering Ilir. Data were collected through observation, questioning, and documentation. As a result of perception, it was found that students’ inventive considering is composed of five markers. Fluency standard is “very good” (83.76%), flexible skill standard is “very good” (89.1%), creative skill standard is “very good” (83.76%) “good” (79.25%).